2000
DOI: 10.2514/2.4515
|View full text |Cite
|
Sign up to set email alerts
|

Design of Fuzzy Logic Guidance Law Against High-Speed Target

Abstract: An advanced guidance law is developed against very high-speed targets. Preliminary studies have shown that the aspect angle of the interceptor at lock-on near 180 deg is a fundamental requirement for achieving small miss distance against a very high-speed target. To meet this requirement, a fuzzy guidance law in midcourse phase that is more similar to human decision making is designed. In terminal phase, a proportional and derivative-type fuzzy terminal guidance law is explored. It is shown that the integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In control applications, fuzzy logic approaches using, if-then, rules can solve complex and practical problems. In recent years, researchers have also attempted to apply it on missile guidance designs [12][13][14][15] . Although, many applications of fuzzy logic theory on missile guidance and control have appeared with growing interest, no application to the terminal guidance with impact angle control problem has been attempted.…”
Section: Fuzzy Logic Controlmentioning
confidence: 99%
“…In control applications, fuzzy logic approaches using, if-then, rules can solve complex and practical problems. In recent years, researchers have also attempted to apply it on missile guidance designs [12][13][14][15] . Although, many applications of fuzzy logic theory on missile guidance and control have appeared with growing interest, no application to the terminal guidance with impact angle control problem has been attempted.…”
Section: Fuzzy Logic Controlmentioning
confidence: 99%
“…The evader is placed at the center of a coordinate and the course is taken at x-axis. From the viewpoint of the approach direction, there are three directions of front (1, 2, 3), right-hand side (4,5,6) and left-hand side (7,8,9). Moreover, from the viewpoint of crossing relation, there are four relations of collision (2,5,8), passing each other just to the right or left side (1, 3), forward crossing (4, 7) and rear crossing (6,9).…”
Section: Horizontal Planementioning
confidence: 99%
“…Fuzzy logic has been applied in the field of aviation (e.g., missile interception, [7][8][9] landing guidance 10) and maneuvering assist 11) ); however, It has not been applied to avoidance problems yet. The output in an avoidance action is calculated not from the differential calculus of a risk function, but is based on an experience rule (rule base) in the fuzzy control.…”
Section: Fuzzy Collision Avoidance Control Lawmentioning
confidence: 99%
“…Optimal control techniques using trajectory shaping have been shown successful for combined midcourse and terminal guidance by Lin and Tsai [4]. Later, Lin and Chen investigated fuzzy guidance control and showed improved insensitivity to model uncertainty [5]. Recently, Hablani demonstrated that predictive endgame guidance was superior to pulse proportional navigation when divert thrusters are used [6].…”
Section: Introductionmentioning
confidence: 98%